Pistachio Extract Improves Neurocognitive Behaviors in Ovariectomized Mice - Elham Hakimizadeh; Faezeh Jandaghi; Mojdeh Hajmohammadi; Iman Fatemi; Ayat Kaeidi; Ali Sham‌sizadeh; Mohammad Allahtavakoli* (Iranian Society of Pharmacognosy, 2019)
Background and objectives: Menopause is associated with depression as well as emotional and memory disorders. Based on the anti-inflammatory and antioxidant effects of pistachio, its effect on depression, cognitive function, anxiety and physical power in ovariectomized mice was investigated. Methods: In the current study, fifty female mice were used. They were aliquoted into five groups: control, ovariectomy (OVX), ovariectomy + DMSO, ovariectomy +10 mg/kg pistachioextract and Ovariectomy +100 mg/kg pistachio extract. In order to prepare the required extract, pistachio nuts were powdered (100 g) and macerated in 1 L of ethanol (80%) for 72 h. Pistachio extract was used orally once a day in ovariectomized mice for sixty days. Anxiety, depression, working memory and physical power were evaluated by the Elevated plus-maze (EPM) test, Forced swimming test (FST), Y maze and swimming exhaustion test, respectively. Results: The results showed that extract of pistachio (more potentially at the dose of 100 mg/kg) decreased anxiety-like behaviors and depression; besides, increase in working memory and physical power was observed in the ovariectomized mice. Conclusion: The findings of the current investigation suggest that pistachio extract could be used as a potential strategy for the attenuation of ovariectomy-related manifestation